2018
DOI: 10.5433/1679-0359.2018v39n2p893
|View full text |Cite
|
Sign up to set email alerts
|

Development of digestive organs of female broilers under varying post-hatch fasting times

Abstract: This study aimed to evaluate the effect of post-hatch fasting time on the weights of body and digestive organs of chicks. Fertile eggs from 62-week-old broiler breeders (Cobb Fast lineage) were incubated and, after hatching, female chicks were randomly divided into six treatments, which corresponded to fasting periods (0, 6, 12, 24, 48, and 72 hours), with 40 chicks per treatment. At 01, 03, 06, and 10 days after hatching, measurements of body weight; residual yolk weight; relative weights of proventriculus + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Similarly to the results found in our study, Ribeiro et al (2018) found that a post-hatching fasting of up to 24 h did not interfere with the weights of digestive organs of 10-day-old female broiler chickens. However, 48-and 72-h post-hatch fasting adversely affected the weight and growth of digestive organs in the birds.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to the results found in our study, Ribeiro et al (2018) found that a post-hatching fasting of up to 24 h did not interfere with the weights of digestive organs of 10-day-old female broiler chickens. However, 48-and 72-h post-hatch fasting adversely affected the weight and growth of digestive organs in the birds.…”
Section: Discussionsupporting
confidence: 91%